STUDI KASUS PENGGUNAAN MEDIA DALAM PEMBELAJARAN PAI DI SATUAN PENDIDIKAN - Riswan; Mardia Hayati (STKIP Subang, 2026)
This research aims to determine the concept, urgency, and implementation steps of a case study on the use of Islamic Religious Education (PAI) learning media in educational institutions. The background of the research is based on the still low utilization of innovative learning media in the PAI learning process, resulting in learning that tends to be conventional and less engaging for students. However, the use of learning media plays a crucial role in increasing students' understanding, interest in learning, and internalization of Islamic values. This research employed a qualitative approach with a case study method, conducting an in-depth study of the phenomenon of the use of Islamic Religious Education (PAI) learning media in educational settings. Data collection techniques were conducted through observation, interviews, and documentation, while data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The results indicate that case studies are highly urgent in PAI learning because they provide a concrete picture of the learning process, the effectiveness of media use, and the challenges faced by teachers and students. The use of learning media such as audio-visual materials, instructional videos, and digital media has been proven to increase student engagement, interest in learning, and understanding of PAI material. Furthermore, systematically implementing case studies, from problem identification to learning evaluation, can assist teachers in developing more effective and modern learning innovations. Thus, case studies are a crucial approach to sustainably improving the quality of Islamic Religious Education (PAI) learning. Keywords: case studies, learning media, Islamic Religious Education, innovative learning, digital media